Prevalence of common mental disorders and associated factors among adults with Glaucoma attending University of Gondar comprehensive specialized hospital tertiary eye care and training center, Northwest, Ethiopia 2020 - Tilahun, Mikias Mered (PLoS One, 2021)
PURPOSE: This study aimed to assess the prevalence of common mental disorders and associated factors among adults with glaucoma at Gondar university comprehensive specialized hospital tertiary eye care and training center. Glaucoma predisposes patients to common mental problems and leads to wasteful, costly and inefficient use of medical services and complications of the diagnoses. So, determining the level and factors associated with common mental disorders among glaucoma patient would help to improve and integrate comprehensive ophthalmic services which address common mental disorder in a follow-up visit. METHODS: An institution-based cross-sectional study was conducted on 495 glaucoma patients selected by using systematic random sampling. Data were collected through face-to-face interview and chart review. Self-reported questionnaire (SRQ-20) was used to assess the presence of common mental disorders. Binary logistic regression analysis was done to identify factors associated with common mental disorders. Variables with P<0.05 were considered as factors significantly associated with common mental disorders. RESULT: Four hundred sixty-eight patients were included in this study with a response rate of 94.54%. The mean age of the participant was 58 ± 14.11 years. The prevalence of common mental disorders was found to be 29.5% (95% CI 25.4–33.3). Female sex (AOR = 3.79, 95% CI: 1.66–8.62) (p-value = 0.001), average monthly income of less than 1200 birr (AOR = 6.05 95% CI: 2.26–16.22) (p-value = 0.001), poor level of social support (AOR = 17.39 95% CI: 7.79–38.82) (p-value = 0.001), moderate and high risk of alcohol use (AOR = 10.42 95%CI: 2.74–39.54) (p-value = 0.001), presence of chronic medical illness (AOR = 3.85 95% CI: 2.07–7.16) (p-value = 0.001), receiving both drug and surgical treatment (AOR = 2.50, 95%CI: 1.30–4.83) (p-value = 0.006) and presence of systemic carbonic anhydrase inhibitors use (AOR = 3.16, 95%CI: 1.65–6.06) (p-value = 0.001) were significantly associated with increased level of common mental disorders. CONCLUSION: Significant numbers of glaucoma patients have CMD and found significantly associated with socio-economic, ocular and systemic clinical factors. Therefore, the integration of psychosocial care into the current treatment of patients with glaucoma would have a significant advantage to help these patients.